2019
DOI: 10.1093/bjsw/bcz041
|View full text |Cite
|
Sign up to set email alerts
|

The Framework of Historical Oppression, Resilience and Transcendence to Understand Disparities in Depression Amongst Indigenous Peoples

Abstract: Given chronic experiences of historical oppression, Indigenous peoples tend to experience much higher rates of depression than the general US population, which then, drives disproportionately high rates of suicide and other health disparities. The purpose of this research was to examine the core components of the culturally grounded Framework of Historical Oppression, Resilience, and Transcendence as they relate to depressive symptoms experienced by Indigenous peoples. As part of a larger convergent mixed-meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 45 publications
(43 reference statements)
0
12
0
Order By: Relevance
“…McKinley (formerly Burnette) and colleagues have developed a framework of historical oppression, resilience, and transcendence (FHORT). This is an American Indianfocused approach, developed over a period of 10 years in collaboration with partner tribal organizations to frame risk and protective factors within this cultural context [18]. The FHORT framework (Figure 1) defines historical oppression to include contemporary oppression (psychological trauma, ACEs, intimate partner violence, and economic inequality) exacerbated by historical traumas such as boarding schools that removed children from their homes and cultural environments.…”
Section: Measuring Historical Oppression As a Clinical Toolmentioning
confidence: 99%
See 1 more Smart Citation
“…McKinley (formerly Burnette) and colleagues have developed a framework of historical oppression, resilience, and transcendence (FHORT). This is an American Indianfocused approach, developed over a period of 10 years in collaboration with partner tribal organizations to frame risk and protective factors within this cultural context [18]. The FHORT framework (Figure 1) defines historical oppression to include contemporary oppression (psychological trauma, ACEs, intimate partner violence, and economic inequality) exacerbated by historical traumas such as boarding schools that removed children from their homes and cultural environments.…”
Section: Measuring Historical Oppression As a Clinical Toolmentioning
confidence: 99%
“…It provides a culturally relevant framework, which can be used to explain, predict, and prevent violence. The FHORT characterizes well-being (harmony across physical, social, psychological, and spiritual domains) as a balance between ecological risk and protective factors [18].…”
Section: Measuring Historical Oppression As a Clinical Toolmentioning
confidence: 99%
“…Indigenous peoples around the globe are resilient, and their identity and culture are a fundamental source of strength. However, the high incidence of mental health issues within this population is troubling, which may be attributed to the historical oppression, colonization and the continuous social, political and environmental challenges that they often face [1]. Besides difficulties associated with colonization and geographical remoteness [2], these Indigenous communities are confronted with a high turnover and a lack of qualified mental healthcare providers [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Family resilience enables families' successful coping under duress; a recent review of family resilience factors identified family communication (i.e., clarity, open emotional expression, and collaborative problem solving) as one essential tool promoting family resilience (Black & Lobo, 2008;Walsh, 2016). Family resilience promotes Indigenous health equity (Burnette, 2018;Burnette & Hefflinger, 2016;Burnette, Renner, & Figley, 2019;Burnette, Roh, et al, 2019;McKinley, Lesesne, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%